Molly's cookbook : a peek at dining in the past with meals you can cook today - Athan, Polly; Bernstein, Rebecca S.; Braun, Terri (Middleton, Wisconsin : Pleasant, 1994)
Make the same foods that Molly made in 1944. This cookbook is filled with recipes, photographs, and party tips
Primary
Keywords: Cooking -- Juvenile literature; Cookery, American -- Juvenile literature; Social life and customs